Naringin ameliorates sodium arsenite-induced renal and hepatic toxicity in rats: decisive role of KIM-1, Caspase-3, TGF-β, and TNF-α. (14th September 2015) - Adil, Mohammad; Kandhare, Amit D.; Visnagri, Asjad; Bodhankar, Subhash L.
Abstract: Chronic exposure of a naturally occurring metal arsenic leads to renal and hepatic diseases. Naringin, a flavanone glycoside, possesses anti-inflammatory and anti-oxidant potential. The aim of this investigation was to evaluate the protective effect of naringin against arsenic-induced renal and hepatic toxicity in rats. Renal and hepatic toxicity was induced in rats by sodium arsenite (5 mg/kg, p.o.). Rats were treated orally with either vehicle or naringin (20, 40, and 80 mg/kg) or Coenzyme Q10 (10 mg/kg) for 28 days. Various biochemical, histological, and molecular biomarkers were assessed in kidney and liver. Treatment with naringin (40 and 80 mg/kg) significantly and dose-dependently restored ( p < 0.01 and p < 0.001) altered levels of kidney (serum creatinine, urine creatinine, BUN, uric acid, and creatinine clearance) and liver function test (AST and ALT) induced by sodium arsenite. Elevated levels of oxido-nitrosative stress in renal and hepatic tissue was significantly and dose-dependently decreased ( p < 0.01 and p < 0.001) by naringin (40 and 80 mg/kg) treatment. It significantly and dose-dependently down-regulated ( p < 0.01 and p < 0.001) renal KIM-1, Caspase-3, TGF-β, and TNF-α mRNA expression. Histopathological alteration induced in kidney and liver by sodium arsenite was reduced by naringin (40 and 80 mg/kg) treatment. In conclusion, naringin treatment ameliorates arsenic-induced renal and hepatic damage in rats due its antioxidant and anti-inflammatory properties via down-regulation of elevated oxido-nitrosative stress, KIM-1, Caspase-3, TGF-β, and TNF-α levels.